PENGARUH BERNYANYI LAGU CUCI TANGAN TERHADAP PELAKSANAAN TEKNIK MENCUCI TANGAN PADA ANAK USIA PRASEKOLAH (5-6 TAHUN) - Christin Jayastri (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2014)
Singing method is one of the learning method by preschool student. Daily attitude very influence to the condition of the children like wash the hand. This research is purpose to know effects of singing hand wash song to hand washing implementation technique to preschool children. This reseach is pre-experiment by the program one group pre-test post test design. The total sample utilized 48 peoples with the total sampling technique. The kind of data is primier data by use the observation sheet. All the children get the lesson of health by singing method 6 times meeting and every meeting sing a song 4 time. The results of this research realize that there are of 36 children (80%) with very bad category before singing songs hand washing. And there were 24 children (53.3%) with good category. Based on analysis data by wilcoxson signed rank test show result that the obtained value p=0.000, which means the are effect of singing hand wash song to hand washing implementation technique to preschool children.